Relaxometric Study Concerning the Action of A Complexant Agent on Petroleum - Flávio Vinicius Crizóstomo Kock; Elói Alves Silva Filho; Eustáquio Vinícius Ribeiro de Castro; Valdemar Lacerda Jr; Lúcio Leonel Barbosa (Global Journal of Energy Technology Research Updates, 2015)
Applying a complexant agent to the contention and bioremediation of petroleum spills, although important for industry, is very rare. Therefore, the aim of this paper is to present a study concerning the influence of a complexant agent, namely chitosan, on petroleum using time-domain nuclear magnetic resonance (TD-NMR). Alterations in the transverse relaxation time (T2) values and peak areas were observed, inferring that the interaction of the complexant agent with petroleum causes destabilization, precipitation of chemical compounds and separation of phases (water and oil). Thus, a novel application involving this spectroscopic technique in the energy field is presented.